Gene polymorphisms, tobacco exposure and oral cancer susceptibility: a study from Gujarat, West India. (28th February 2013) - Singh, RD; Haridas, N; Shah, FD; Patel, JB; Shukla, SN; Patel, PS
<x xml:space="preserve">Abstract</x> Polymorphic variability in the enzymes involved in biotransformation of tobacco‐related pro‐carcinogens plays an important role in modulating oral cancer susceptibility. CYP1A1*2A, CYP1A1*2C, GSTM1 and GSTT1 polymorphisms were determined in 122 oral carcinoma cases and 127 controls from Gujarat, West India using PCR‐based methods. The results revealed that the polymorphic variants of CYP1A1 gene did not show association towards oral cancer risk. The GSTM1 and GSTT1 null genotypes were found to be over‐represented in patients than controls, suggesting a moderate increase in risk of oral cancer. The oral cancer risk was significantly increased in the patients having either alone or concurrent deletion of GSTM1 and GSTT1. The results also suggested significant association between tobacco habits, especially chewing, variant genotypes of CYP1A1, GSTM1 and GSTT1 and oral cancer risk. Our data have provided evidence that GST polymorphism modified the susceptibility to oral cancer and individuals with variant genotypes of the three genes with tobacco habits are at significant risk of developing oral cancer.